Lineage-reprogramming of pericyte-derived cells of the adult human brain into induced neurons - Karow, Marisa; Schichor, Christian; Beckervordersandforth, Ruth; Berninger, Benedikt (Journal of Visualized Experiments, 2014)
Direct lineage-reprogramming of non-neuronal cells into induced neurons (iNs) may provide insights into the molecular mechanisms underlying neurogenesis and enable new strategies for in vitro modeling or repairing the diseased brain. Identifying brain-resident non-neuronal cell types amenable to direct conversion into iNs might allow for launching such an approach in situ, i.e. within the damaged brain tissue. Here we describe a protocol developed in the attempt of identifying cells derived from the adult human brain that fulfill this premise. This protocol involves: (1) the culturing of human cells from the cerebral cortex obtained from adult human brain biopsies; (2) the in vitro expansion (approximately requiring 2-4 weeks) and characterization of the culture by immunocytochemistry and flow cytometry; (3) the enrichment by fluorescence-activated cell sorting (FACS) using anti-PDGF receptor-? and anti-CD146 antibodies; (4) the retrovirus-mediated transduction with the neurogenic transcription factors sox2 and ascl1; (5) and finally the characterization of the resultant pericyte-derived induced neurons (PdiNs) by immunocytochemistry (14 days to 8 weeks following retroviral transduction). At this stage, iNs can be probed for their electrical properties by patch-clamp recording. This protocol provides a highly reproducible procedure for the in vitro lineage conversion of brain-resident pericytes into functional human iNs.
EVALuna2:26324